Analysis of the Behavior of Carbon Nanotubes on Cementitious Composites. (27th August 2013) - de Morais, Jorge Fernandes; Haddad, Assed Naked; Haurie, Laia
Abstract : Nanotechnology has brought significant innovations in science and engineering. Carbon nanotube has been considered a new and outstanding material in nanoscience field with great potential application in the construction industry. The main objective of this study is to analyze the behavior of cementitious materials produced with the insertion of carbon nanotubes of multiple walls in different concentrations and compare their physic-mechanical properties with plain mortar. This research covers the examination of nanoscale cement products and the use of carbon nanotubes to increase the strength and durability of cementitious composites. Three different ratios of carbon nanotubes have been searched: 0.20, 0.40, and 0.60%. To evaluate the mechanical properties of the samples, destructive and nondestructive tests were carried out to obtain compressive strength, tensile strength by diametrical compression, and dynamic modulus of elasticity as well as to determine their deformation properties. Methods of instrumentation such as scanning electron microscopy and porosity were also used in the analysis of microstructure of the materials. The study presents graphs, tables, and figures describing the behavior of CNT added to mortars samples, allowing a better understanding of the use of this new material in the construction industry.